2022
DOI: 10.1159/000522231
|View full text |Cite
|
Sign up to set email alerts
|

miR-142-5p Encapsulated by Serum-Derived Extracellular Vesicles Protects against Acute Lung Injury in Septic Rats following Remote Ischemic Preconditioning via the PTEN/PI3K/Akt Axis

Abstract: This study intends to investigate the effects of miR-142-5p encapsulated by serum-derived extracellular vesicles (EVs) on septic acute lung injury (ALI) following remote ischemic preconditioning (RIPC) through a PTEN-involved mechanism. ALI was induced in rats by lipopolysaccharide (LPS) injection, 24 h before which RIPC was performed via the left lower limb. Next, the binding affinity between miR-142-5p and PTEN was identified. EVs were isolated from serum and injected into rats. The morphology of lung tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…RIPC successfully induces ischemic tolerance not only in the brain, but also in the heart [ 151 ], kidneys [ 152 ], lungs [ 153 ], and liver [ 154 ], which seems to suggest that repeated ischemic preconditioning of one artery may have induced ischemic tolerance throughout the body. How does this protective effect extend from local to other areas?…”
Section: Discussionmentioning
confidence: 99%
“…RIPC successfully induces ischemic tolerance not only in the brain, but also in the heart [ 151 ], kidneys [ 152 ], lungs [ 153 ], and liver [ 154 ], which seems to suggest that repeated ischemic preconditioning of one artery may have induced ischemic tolerance throughout the body. How does this protective effect extend from local to other areas?…”
Section: Discussionmentioning
confidence: 99%
“…85 Zhu et al used the same pretreatment strategy as Pan et al and found miR-142-5p reduced the level of pro-inflammatory factors and neutrophil infiltration, it also relieved pulmonary oedema via the PTEN/PI3K/Akt axis. 86 In addition, ADMSC subjected to hypoxic preconditioning promoted mmu_circ_0001295 expression in Exos, which attenuated renal vascular leakage and inflammation in kidney and improved kidney function. Early clinical intervention may improve outcomes and reduce the mortality of patients with sepsis.…”
Section: How Does Pretreatment Of Extracellular Vesicles Treat Sepsis?mentioning
confidence: 99%
“…Thus, miRNAs can affect cellular functions beyond the scope of the intracellular posttranscriptional modifications, which they were originally discovered to perform three decades ago [ 1 ]. This expanded understanding of miRNAs has helped reveal their role in acute inflammation, providing new opportunities to explore treatments of immune dysregulation, particularly in sepsis [ 10 , 49 , 50 ]. This section of the review will focus on the activity of extracellular miRNAs in vesicles and bound by proteins.…”
Section: Mechanisms Of Extracellular Mirna Actionsmentioning
confidence: 99%
“…Another miRNA, miR-142-5p, can travel inside extracellular vesicles to bind with and inhibit phosphatase and tensin homolog (PTEN) activity, thus promoting phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) activity [ 50 ]. In a mouse model of cecal ligation and puncture (CLP)-induced sepsis, exosomal miR-93-5p inhibited lysine-specific demethylase 6B (KDM6B) , reducing TNF-α production and acute kidney injury (AKI) [ 75 ].…”
Section: Extracellular Mirna As Therapeutic Targetsmentioning
confidence: 99%